2003
DOI: 10.1081/al-120023617
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Microsystem for Trace Elements Monitoring

Abstract: The development of a voltammetric microsystem for monitoring and speciation studies of trace elements in natural waters is presented. This system was designed to provide an efficient coupling of the square-wave anodic stripping voltammetry (SWASV) detection with the permeation liquid membrane (PLM) technique. It consists of a voltammetric microcell, based on a gel-integrated Ir(Hg) micro-disk array, a PLM and two micromachined channels for the sample and strip solutions respectively. The analytical performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…1). It has been shown that such a gel not only protects the electrode against unspecific interferences, but it may also be chemically modified in order to obtain specific properties beneficial for voltammetric measurements [8][9][10]. Such GIME or analogous systems are thus very promising for analysis in complicated media.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1). It has been shown that such a gel not only protects the electrode against unspecific interferences, but it may also be chemically modified in order to obtain specific properties beneficial for voltammetric measurements [8][9][10]. Such GIME or analogous systems are thus very promising for analysis in complicated media.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we developed a microcell coupling the permeation liquid membrane (PLM) technique with voltammetric detection for trace metal speciation [10][11][12]. Briefly, the metals are transported from an aqueous test solution through the PLM by carrier-aided transport, to finally become chemically accumulated into a so-called strip solution [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some selected applications to detect Zn, Pb, Cd, Cu and Tl(I) in aquatic systems are reported in refs. [142][143][144][145][146][147][148].…”
Section: Arrays and Ensembles Of Microelectrodesmentioning
confidence: 99%
“…Microanalytical systems can be defined as systems where the sample preparation and detection are integrated in a single device. Buffle's group has been heavily involved in this area [48,86,87].…”
Section: Microanalytical Systemmentioning
confidence: 99%